Jackie & me - Bayard, Louis (Algonquin Books of Chapel Hill, 2022)
"A historical novel depicting a naïve, career-girl version of Jackie Kennedy and her iconic marriage-in-the-making to an elusive John F. Kennedy, narrated by Jack's best friend and fixer, Lem Billings"--